PENGARUH PENGELUARAN PEMERINTAH PADA SEKTOR PENDIDIKAN DAN KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KOTA BANDUNG (2013-2022) - Nursita, Lisa; Wael, Marwiyah Windah; Amanda, Dewi; Wahyuni, Rema; Amri, Muhammad (STKIP Persada Khatulistiwa Sintang, 2025)
In the midst of the dynamics of the country's development, the Human Development Index (HDI) is an important indicator for measuring the success and quality of people's lives. This research aims to determine and analyze the influence of government spending in the education and health sectors on the Human Development Index (HDI) in Bandung City in 2013-2022. In this research, the method used is multiple linear regression. Based on the research results, it shows that the Bandung city government's partial expenditure on the education sector and government expenditure on the health sector have a positive and significant effect on HDI. Then, simultaneously or concurrently, government spending on education and health has a significant effect on the HDI in the Bandung City sector in the 2013-2022 period. Budget allocation policies, especially in the Education and Health sectors, have increased which has resulted in the human development index in the city of Bandung also increasing every year. Government budget allocations in education aim to increase access to knowledge and skills, while spending on health aims to provide access to health services to improve community welfare. Both contribute to increasing the human development index in Bandung City.